Changes in inflammatory factors (IL-1β, IL-6, IL-8, TNF-α, PCT), vascular endothelial function (NO, ∆D, vWF, and ET-1), and T-lymphocyte subsets before and after treatment in patients with acute respiratory failure - Wang, Jie; Chen, Yunxia; Yuan, Xinyu; Sun, Sisi; Ding, Wenjuan; Dai, Ningning (Journal of Medical Biochemistry, 2025)
Background: Given the critical importance of inflammation, immune and endothelial function in acute respiratory failure (ARF), it is essential to evaluate therapeutic strategies that target these pathways to confirm their application value. This study aimed to investigate the impact of chain management guided by risk warning on inflammatory markers (interleukin [IL]-1β, IL-6, IL-8, tumor necrosis factor [TNF]-α, and procalcitonin [PCT]), vascular endothelial function, blood gas parameters, and T lymphocyte subsets in patients with ARF.  Methods: A retrospective analysis was conducted on 101 ARF patients admitted between October 2023 and December 2024. The patients were categorized into two groups: a conventional group (55 cases, receiving standard risk warning management) and a chain group (46 cases, undergoing chain management guided by risk warning). Levels of inflammatory factors and vascular endothelial markers (nitric oxide [NO], endothelin-1 [ET-1], etc.) were measured using enzyme-linked immunosorbent assay (ELISA), blood gas function was evaluated with a blood gas analyzer, and T lymphocyte subsets (CD3+, CD4+, and CD8+) were analyzed via flow cytometry.  Results: Compared to the conventional group, the chain group demonstrated significantly shorter durations of mechanical ventilation and ICU stays (P < 0.05). Moreover, the chain group exhibited more pronounced reductions in inflammatory factors, including IL-1β, TNF-α, and PCT (P < 0.05). Improvements in vascular endothelial function were also more evident in the chain group, with higher NO levels and lower ET-1 levels (P < 0.05). Additionally, the chain group achieved better blood gas outcomes, characterized by higher PaO2 and lower PaO2 levels (P < 0.05), as well as greater increases in CD3+ and CD4+ cell counts (P < 0.05). However, no significant inter-group difference was observed in the incidence of complications (P > 0.05).  Conclusion: Chain management guided by risk warning effectively mitigates inflammatory responses and enhances vascular immune function, endothelial function in ARF patients through multi-targeted interventions.
Keywords: acute respiratory failure; inflammatory factors; vascular endothelial function; T lymphocyte subsets